Long-Term Functioning of Patients with Aneurysmal Subarachnoid Hemorrhage: A 4-yr Follow-up Study. (February 2016) - Boerboom, Wendy; Heijenbrok-Kal, Majanka H.; Khajeh, Ladbon; van Kooten, Fop; Ribbers, Gerard M.
ABSTRACT: Objectives: The aim was to study changes over time for multiple outcomes based on the International Classification of Functioning, Disability, and Health in patients with aneurysmal subarachnoid hemorrhage and to compare long-term outcomes with norms. Design: A prospective cohort study with 4-yr follow-up was conducted. Main outcome measures were as follows: Center for Epidemiologic Studies–Depression Scale, Fatigue Severity Scale, Trail Making Test A and B, Barthel Index, Sickness Impact Profile-68, Impact on Participation and Autonomy Questionnaire, Social Support List-12, Multidimensional Health Locus of Control Scales, COOP-WONCA Charts, and Short Form-36 Health Survey. Results: Seventy-six patients with aneurysmal subarachnoid hemorrhage were included. Measurements were done at T1 = 0.4 yrs (SD, 0.3 yrs) and T2 = 3.9 yrs (SD, 0.7 yrs) after onset. Significant improvements over time were found for Barthel Index (T1 = 18.5; T2 = 19.5; P = 0.023), Trail Making Test B (T1 = 119.4; T2 = 104.6; P = 0.025), Social Support List-12 total score (T1 = 31.1; T2 = 32.7; P = 0.042) and esteem support (T1 = 10.2; T2 = 10.9; P = 0.027), Multidimensional Health Locus of Control Scales (physician-orientation) (T1 = 21.8; T2 = 19.2; P = 0.020), and Short Form-36 Health Survey (role-emotional) (T1 = 54.6; T2 = 73.9; P = 0.048). Center for Epidemiologic Studies–Depression Scale, Fatigue Severity Scale, Sickness Impact Profile-68, and Short Form-36 Health Survey scores remained stable over time. A decline was found for COOP-WONCA (overall-health) (T1 = 2.3; T2 = 2.7; P = 0.021). At 4-yr follow-up, proportions of depression (27%) and fatigue (60%) were larger and scores on the Fatigue Severity Scale (mean [SE], 4.3 [0.2]), Trail Making Test A (mean [SE], 51.3 [3.9]), and Trail Making Test B (mean [SE], 104.4 [0.2]) were significantly worse than norm scores. Conclusions: Many patients with aneurysmal subarachnoid hemorrhage had fairly good long-term outcomes, but problems in executive functioning, mood, and fatigue still exist at long-term follow-up.